PENGGUNAAN KATA SAPAAN BAHASA MINANGKABAU DAN IMPLIKASINYA TERHADAP KESANTUNAN BERBAHASA MASYARAKAT DESA KAMPUNG BARU KECAMATAN PARIAMAN TENGAH KOTA PARIAMAN - Novendra, Novendra; Ermanto, Ermanto; Ngusman, Ngusman (Universitas Negeri Padang, 2017)
This study was conducted to describe the shape and use of kinship and unkinship greeting words in the language Minangkabau villagers of Kampung Baru.The use of the word greeting kinship consists of greeting based on the nuclear family and the extended family based. Greetings unkinship include common greeting, occupation, religion, and customs. The research is a qualitative research with descriptive methods. The informants are two women and one man.Background this study is the village of Kampung Baru Pariaman Tengah District Pariaman Downtown. The instrument of this study is the researchers themselves to use a tape recorder, recording sheet, and stationery. The data collection method used in this study conversation with fishing techniques. Data validation study using triangulation techniques. Analyzing data of this research through the following steps: (1) a data inventory phase; (2) the stage of data classification; (3) the stage of data description. The results of this study as follows: found (1) 82 shapes and the use of the word greeting kinship, which consists of 22 forms of the word greeting kinship based on the nuclear family, 60 shapes and the use of the word greeting kinship based on the extended family. (2) 41 shapes and the use of the word greeting unkinship, namely, 11 shapes and the use of the word common greeting, 13 shapes and the use of the word greeting positions, 12 shapes and the use of the word religious greeting, five shapes and using the customary greeting. Implications of the use of the word greeting Minangkabau language in terms of kinship and unkinship greeting word still used in accordance with the politeness prevailing in society the village of Kampung Baru.Keywords: greeting words, kinship, unkinship, implication, languangeÂ Â Â Minangkabau.